منهج الدعوة فى تفسير الشيخ سعيد حوى : دراسة تحليلية - Mashhuri bin al-Haj Mas'ud (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2012)
This research explores the methodology of da'wah in Sheikh Sa'id Hawa's Qur'anic tafsir as an analytical study which follows an induction and an analytical approach. The main aim of this study is to extract his ideas related to the topic contained in his Qur'Énic exegesis entitled al-Asas fi al-Tafsir (Principles of Exegesis). The research found the methodology of da'wah in his tafsir emphasizes on the characteristic of da'wah, its various means and general features used by Sheikh Sa'id Hawa in his tafsir. He appeals upon all Muslims to renew their way of dealing with Allah SWT and with other fellow human beings on the principles of Qur'anic teaching. In addition, the tafsir also explains the way of the Qur'an that eliminates the jahili influences and corrects their methodological and theoretical thought. Moreover, it requires Muslim preachers to introduce Islamic religion to non-Muslims which could be done in many ways such as pondering upon the natural phenomena and discussing with the use of wisdom and good exhortation. It finally outlines the significance of intellectual, spiritual as well as behavioral aspects that should be imbedded in the personality of da'iyyah to achieve successful in conveying the message to others.